Istifadah Tathbiqat Quizizz fi Taqwim Taâ€™lim Al-Lughah Al-â€˜Arabiyyah - Al Ahqaf, Muhammad Infithar; Darmawaty, Ridha (HuRuf Journal : International Journal of Arabic Applied Linguistic, 2022)
Online learning is an alternative in Arabic learning during the COVID-19. To see the progress of students' learning, it is necessary to evaluate online learning by utilizing the mediaone of them is the application Quizizz. This application has adequate features to be used as a means of delivering interesting and fun Arabic learning materials and evaluations. The purpose ofÂ  this article is to describe the use of the Quizizz application as an online-based evaluation medium for Arabic learning and its possible application in Arabic learning. Data were collected,analyzed, categorized, and concluded through a literature review, both from books and journals related to the evaluation of learning, especially in Arabic using the application Quizizz. This study shows that the evaluation of test-based Arabic learning can be done through the application Quizizz by maximizing the features contained in it, and supported by teacher guidance. Utilization of this application will be maximized if the pro version is implemented to be able to upload sound and video. ÙŠØ¹Ø¯ ØªØ¹Ù„ÙŠÙ… Ø§Ù„Ù„ØºØ© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© Â Ø¹Ø¨Ø± Ø§Ù„Ø¥Ù†ØªØ±Ù†Øª Ø¨Ø¯ÙŠÙ„Ø§Ù‹ Â Ù„Ù„ØªØ¹Ù„ÙŠÙ… Ø§Ù„Ù…Ø¨Ø§Ø´Ø± Ø£Ø«Ù†Ø§Ø¡ Ø§Ù„Ø¬Ø§Ø¦ØØ©. Ù„Ù…Ø¹Ø±ÙØ© ØªØ±Ù‚ÙŠØ© ÙƒÙØ§Ø¡Ø© ØªØ¹Ù„Ù… Ø§Ù„Ø·Ù„Ø§Ø¨ ÙÙ…Ù† Ø§Ù„Ø¶Ø±ÙˆØ±ÙŠ Ø£Ù† ØªÙ‚ÙŠÙŠÙ… Ø§Ù„ØªØ¹Ù„Ù… Ø¹Ø¨Ø± Ø§Ù„Ø¥Ù†ØªØ±Ù†Øª Ø¨Ø§Ø³ØªÙØ§Ø¯Ø© Ø§Ù„ÙˆØ³Ø§Ø¦Ø· Ø§Ù„Ø¥ÙØªØ±Ø§Ø¶ÙŠ Ù…Ø«Ù„ ØªØ·Ø¨ÙŠÙ‚Ø§Øª Quizizz.. ØªØØªÙˆÙŠ Ù‡Ø°Ù‡ Ø§Ù„ØªØ·Ø¨ÙŠÙ‚Ø§Øª Ø£Ø¯ÙˆØ§Øª Ù…ØªÙ…ÙŠØ²Ø© Ùˆ Ù…Ù„Ø§Ø¦Ù…Ø© Â Ù„Ø§Ø³ØªØ®Ø¯Ø§Ù…Ù‡Ø§ ÙƒÙˆØ³ÙŠÙ„Ø© ØªÙ‚Ø¯ÙŠÙ… Ø§Ù„Ù…ÙˆØ§Ø¯ Ø§Ù„ØªØ¹Ù„ÙŠÙ…ÙŠØ© Ùˆ ØªÙ‚ÙˆÙŠÙ… Ø§Ù„ØªØ¹Ù„ÙŠÙ… Â Ø§Ù„Ù…Ù…ØªØ¹Ø©. Â ÙØ§Ù„Ù‡Ø¯Ù Ù‡Ø°Ø§ Ø§Ù„Ø¨ØØ« ÙˆØµÙ Ø§Ø³ØªÙØ§Ø¯Ø© Â ØªØ·Ø¨ÙŠÙ‚Ø§Øª Quizizz Â ÙƒÙˆØ³ÙŠÙ„Ø© ØªÙ‚ÙˆÙŠÙ… Ø¹Ø¨Ø± Ø§Ù„Ø¥Ù†ØªØ±Ù†Øª Ù„ØªØ¹Ù„ÙŠÙ… Ø§Ù„Ù„ØºØ© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© Ùˆ Ø¥Ù…ÙƒØ§Ù†ÙŠØ§Øª Ø§Ù„ØªØ·Ø¨ÙŠÙ‚ Â Â ÙÙŠ Ù…Ø¬Ø§Ù„ ØªØ¹Ù„ÙŠÙ… Ø§Ù„Ù„ØºØ© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ©. Â Ù‚Ø§Ù… Ù‡Ø°Ø§ Ø§Ù„Ø¨ØØ« Ø¨Ù…Ù†Ù‡Ø¬ Ø§Ù„Ø¨ØØ« Ø§Ù„Ù…ÙƒØªØ¨ÙŠ Ø¨Ø¬Ù…Ø¹ Ø§Ù„Ø¨ÙŠØ§Ù†Ø§ØªÂ  Ù…Ù† Ø§Ù„Ù…ØµØ§Ø¯Ø± Ø§Ù„Ø£ÙˆÙ„ÙŠØ© ÙˆØ§Ù„Ø«Ø§Ù†ÙˆÙŠØ© Ù…Ù† Ø®Ù„Ø§Ù„ Ø¯Ø±Ø§Ø³Ø© Ø£Ø«Ù†Ø§Ø¡ Ø§Ù„ØªØ¹Ù„ÙŠÙ… ÙˆØ£ÙˆØ±Ø§Ù‚ Ø§Ù„Ø¨ØÙˆØ« Ø§Ù„Ù…ØªØ¹Ù„Ù‚Ø© Ø¨ØªÙ‚ÙˆÙŠÙ… Ø§Ù„ØªØ¹Ù„ÙŠÙ… ØŒ ÙˆØ®Ø§ØµØ© Ø¨Ø§Ù„Ù„ØºØ© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© Ø¨Ø§Ø³ØªØ®Ø¯Ø§Ù… ØªØ·Ø¨ÙŠÙ‚Ø§Øª Quizizz. ÙØ§Ø³ØªÙ†ØªØ¬ Ù‡Ø°Ø§ Ø§Ù„Ø¨ØØ« Ø¥Ù…ÙƒØ§Ù†ÙŠØ§Øª ØªØ·Ø¨ÙŠÙ‚Â  ØªÙ‚ÙˆÙŠÙ… ØªØ¹Ù„ÙŠÙ… Ø§Ù„Ù„ØºØ© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© Ø§Ù„Ù‚Ø§Ø¦Ù… Ø¹Ù„Ù‰ Ø§Ù„Ø§Ø®ØªØ¨Ø§Ø± Ù…Ù† Ø®Ù„Ø§Ù„ ØªØ·Ø¨ÙŠÙ‚Ø§Øª Quizizz Ø¨Ø£Ø¯ÙˆØ§Øª Ø§Ù„Ù…ØªÙ…ÙŠØ²Ø© Ø§Ù„ÙˆØ§Ø±Ø¯Ø© ÙÙŠÙ‡Ø§ ÙˆØ¯Ø¹Ù…Ù‡Ø§ ØªØØª Ø¥Ø´Ø±Ø§Ù Ø§Ù„Ù…Ø¹Ù„Ù…. ÙˆØ²Ø§Ø¯Øª Ø§Ù„Ø¥Ø³ØªÙØ§Ø¯Ø© Ø¨Ø§Ø³ØªØ®Ø¯Ø§Ù… Ø¥ØµØ¯Ø§Ø± Ø§Ù„ØªØ·Ø¨ÙŠÙ‚Ø§Øª Ø§Ù„Ù…ØØªØ±Ù Ø¨Ø£ÙƒØ«Ø± Ù…Ù† Ø§Ù„Ø¢Ø¯ÙˆØ§Øª Ù…Ù† Ù„Ù„ØªØ³Ø¬ÙŠÙ„ Ø§Ù„Ø£ØµÙˆØ§Øª ÙˆØ§Ù„Ù…Ù‚Ø·ÙŠØ¹ Ù…Ù† ÙÙŠØ¯ÙŠÙˆÙ‡Ø§Øª.Â 